ECONOMICALLY SENSIBLE ALLOCATION OF RESOURCES FOR OVERLAY ROUTING RELAY NODES (International Journal of Food and Nutritional Sciences, 2021)
The Internet is widely regarded as the most popular application on a worldwide scale. The major goal of the Internet is to provide complete services and a diverse range of information and communication capabilities, all while maintaining a high level of accessibility and responsiveness. Diverse and continuous efforts are being undertaken to identify and remedy issues affecting the accessibility of the Internet. Connection and router issues, as well as a variety of other issues, have the greatest impact on Internet performance. One potential option for improving Internet behavior is the widespread deployment of intelligent routers throughout network infrastructure, which would efficiently manage and control traffic flow by interacting with other intermediary devices. Intelligent nodes, also known as relay nodes or overlay nodes, allow the traversal of overlay paths, resulting in the formation of an overlay network. The aforementioned nodes have dynamic operational capabilities and add functionality to the existing infrastructure. Overlay Routing Resource Allocation (ORRA) is a versatile architecture that can be deployed to a wide range of applications while requiring less maintenance than other overlay systems such as Resilient Overlay Network (RON) and Detour.